Pengaruh Kepemilikan Saham Manajerial Dan Kepemilikan Saham Intitusional Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2011-2014) - Pamarozi, Hanif; , Dr. Syamsudin, M.M (2016)
The purpose of this study is to empirically examine the influence of Managerial Stock Ownership and Stock Ownership Institutional Against Values manufacturing company listed on the Stock Exchange Iindonesia. The period used in this study is 4 (four) years, ie from 2011 to 2014. The population in this research is manufacturing companies listed in Indonesia Stock Exchange. The sampling is done by using purposive sampling method. The study period from 2011 to 2014. The data were analyzed using multiple linear regression method. The results of this study show that: 1). managerial ownership affect the value of companies in the manufacturing companies listed in Indonesia Stock Exchange. The results of this study support the research Eau De Toilette (2008), 2). institutional share ownership does not affect the value of companies in the manufacturing companies listed on the Indonesian stock exchange. The results of this study do not support the research Chu (2005). 3). Simultaneously or jointly Shareholding Managerial and Institutional share ownership does not affect the Company's value in the companies listed in the Indonesia Stock Exchange. Keywords: managerial ownership, institutional ownership and firm value